Fabrication of single- and multilayer MoS2 film-based field-effect transistors for sensing NO at room temperature - Li, Hai (2013)
Single- and multilayer MoS2 films are deposited onto Si/SiO2 using the mechanical exfoliation technique. The films were then used for the fabrication of field-effect transistors (FETs). These FET devices can be used as gas sensors to detect nitrous oxide (NO). Although the single-layer MoS2 device shows a rapid response after exposure to NO, the current was found to be unstable. The two-, three-, and four-layer MoS2 devices show both stable and sensitive responses to NO down to a concentration of 0.8 ppm.